Fiscal policy in models of economic growth: theory and evidence - Kneller, Richard (1998)
Growth models contain strong predictions regarding the effect of fiscal policy on the steady state growth path. Fiscal policies have no effect on the steady state growth rate in the neoclassical model whereas fiscal policy does feature in the steady state of endogenous growth models. The number of alternative policies which have been found to effect growth in the endogenous growth models is large as one of the few restrictions placed upon policy in the models is which sector of the model is affected, demand or supply. Only policies that are included in the supply side of the model affect the growth rate.